2015
DOI: 10.1159/000439543
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Hybrid SPECT/CT Lung Perfusion Scintigraphy in Pulmonary Embolism Diagnosis

Abstract: Background: Pulmonary embolism (PE) is diagnosed either by ventilation/perfusion (V/Q) scintigraphy or pulmonary CT angiography. One of the imaging methods used in nuclear medicine is hybrid SPECT/CT scintigraphy. Objectives: The aim of this study was to evaluate the utility of SPECT/CT(Q) scintigraphy in the diagnosis of PE and to compare SPECT/CT(Q) with planar(Q) and SPECT(Q) methods. Methods: The study group consisted of 109 consecutive patients suspected of having PE referred for performing lung scintigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 18 publications
0
52
2
1
Order By: Relevance
“…Cobes et al retrospectively analyzed V/Q SPECT/CTs in 5 patients hospitalized with COVID-19 and determined that V/Q SPECT/CT could play a role diagnosing embolic complications while following meticulous hygiene [ 22 ]. However, combining a low-dose chest CT with Q-only SPECT can also satisfactorily demonstrate etiologies of potential non-embolic false positive results, such as pulmonary emphysema or bullous disease [ 23 ]. Ventilation studies can contaminate staff members and equipment and in a high-volume nuclear medicine institution, the necessary decontamination steps may not be offset by the benefit of ventilation imaging in some patients during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobes et al retrospectively analyzed V/Q SPECT/CTs in 5 patients hospitalized with COVID-19 and determined that V/Q SPECT/CT could play a role diagnosing embolic complications while following meticulous hygiene [ 22 ]. However, combining a low-dose chest CT with Q-only SPECT can also satisfactorily demonstrate etiologies of potential non-embolic false positive results, such as pulmonary emphysema or bullous disease [ 23 ]. Ventilation studies can contaminate staff members and equipment and in a high-volume nuclear medicine institution, the necessary decontamination steps may not be offset by the benefit of ventilation imaging in some patients during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a similar sensitivity and specificity to Lu et al (100 and 83%, respectively) concluding that Q-SPECT/CT imaging had a high diagnostic efficacy in evaluating patients suspected to have PE. In addition, the inclusion of a chest CT (even at low dose) adds value by characterizing acute pulmonary pathology which could account for the patient’s clinical presentation [ 23 ]. In addition, based on the current European Association of Nuclear Medicine guidelines, Q-only SPECT is already recommended as standard of care, for example in pregnant patients with suspected PE [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 84 patients, SPECT/CT yielded a significantly higher diagnostic accuracy for PE (sensitivity 100% and specificity 83%) than planar and SPECT scans. [77] More recently, SPECT/CT has been used to evaluate CTEPH. [78] A study of 15 patients with precapillary PH and 11 healthy controls calculated a perfusion redistribution index (PRI) using SPECT/CT images.…”
Section: Novel Imaging Modalitiesmentioning
confidence: 99%
“…There have been few studies on the utility of SPECT/CT in the diagnosis of PTE, and there are no definitive recommendations regarding the method. However, it is believed that SPECT/CT has a high (99%) accuracy for the diagnosis, with a sensitivity of 97-100% and a specificity of 83-100% ( 19 , 20 ) .…”
Section: Imaging Evaluation Of Patients With Suspected Ptementioning
confidence: 99%